In Situ Modulation of NiFeOOH Coordination Environment for Enhanced Electrocatalytic‐Conversion of Glucose and Energy‐Efficient Hydrogen Production - Ning Wei; Sufeng Zhang; Xue Yao; Qinglu Li; Nan Li; Jinrui Li; Dingjie Pan; Qiming Liu; Shaowei Chen; Scott Renneckar (Advanced Science)
Abstract Glucose electrocatalytic‐conversion reaction (GCR) is a promising anode reaction to replace the slow oxygen evolution reaction (OER), thus promoting the development of hydrogen production by electrochemical water splitting. Herein, NiFe‐based metal‐organic framework (MOF) is used as a precursor to prepare W‐doped nickel‐iron phosphide (W‐NiFeP) nanosheet arrays by ion exchange and phosphorylation, which exhibit a high electrocatalytic activity toward the hydrogen evolution reaction (HER), featuring an overpotential of only −179 mV to achieve the current density of 100 mA cm−2 in alkaline media. Notably, electrochemical activation of W‐NiFeP facilitates the in situ formation of phosphate groups producing W,P‐NiFeOOH, which, in conjunction with the W co‐doped amorphous layers, leads to a high electrocatalytic performance toward GCR, due to enhanced proton transfer and adsorption of reaction intermediates, as confirmed in experimental and theoretical studies. Thus, the two‐electrode electrolyzer of the W‐NiFeP/NF||W,P‐NiFeOOH/NF for HER||GCR needs only a low cell voltage of 1.56 V to deliver 100 mA cm−2 at a remarkable hydrogen production efficiency of 1.86 mmol h−1, with a high glucose conversion (98.0%) and formic acid yields (85.2%). Results from this work highlight the significance of the development of effective electrocatalysts for biomass electrocatalytic‐conversion in the construction of high‐efficiency electrolyzers for green hydrogen production.